Health workers' attitudes toward sexual and reproductive health services for unmarried adolescents in Ethiopia - Tilahun Mesfin; Mengistie Bezatu; Egata Gudina; Reda Ayalu A (BMC, 2012)
Abstract Background Adolescents in developing countries face a range of sexual and reproductive health problems. Lack of health care service for reproductive health or difficulty in accessing them are among them. In this study we aimed to examine health care workers' attitudes toward sexual and reproductive health services to unmarried adolescents in Ethiopia. Methods We conducted a descriptive cross-sectional survey among 423 health care service providers working in eastern Ethiopia in 2010. A pre-tested structured questionnaire was used to collect data. Descriptive statistics, chi-square tests and logistic regression were performed to drive proportions and associations. Results The majority of health workers had positive attitudes. However, nearly one third (30%) of health care workers had negative attitudes toward providing RH services to unmarried adolescents. Close to half (46.5%) of the respondents had unfavorable responses toward providing family planning to unmarried adolescents. About 13% of health workers agreed to setting up penal rules and regulations against adolescents that practice pre-marital sexual intercourse. The multivariate analysis indicated that being married (OR 2.15; 95% CI 1.44 - 3.06), lower education level (OR 1.45; 95% CI 1.04 - 1.99), being a health extension worker (OR 2.49; 95% CI 1.43 - 4.35), lack of training on reproductive health services (OR 5.27; 95% CI 1.51 - 5.89) to be significantly associated with negative attitudes toward provision of sexual and reproductive services to adolescents. Conclusions The majority of the health workers had generally positive attitudes toward sexual and reproductive health to adolescents. However, a minority has displayed negatives attitudes. Such negative attitudes will be barriers to service utilization by adolescents and hampers the efforts to reduce sexually transmitted infections and unwanted pregnancies among unmarried adolescents. We therefore call for a targeted effort toward alleviating negative attitudes toward adolescent-friendly reproductive health service and re-enforcing the positive ones.